Customer-related durability test of semi-trailer engine based on failure mode. (February 2021) - Han, Yu; Lin, Yier; Zhang, Ce; Wang, DengFeng
Highlights: This paper studies a durability test method of trailer engine. Determine the test route of the engine covering the strength of 95% users in china, by Fleet Measurement of 23 customs. Optimize of engine load spectrum, bench test load spectrum and load matrix under user operating conditions, considering the damage of high cycle fatigue, thermal mechanical fatigue, wear-abrasive, deposits. The problem of equivalent between bench test method and 2 million km user operating conditions is solved. Abstract: This paper studies a durability test method of semi-trailer engine. According to the principle that rig test damage is equal to customers damage target, the durability assessment test method of semi-trailer engine on rig test is established. Determine the test tracts of the engine covering the customers' strength of 95th% in china as the target tracts, by Fleet Measurement of 19 customers. The data of the engine is acquired by Field Measurement with full-channel vehicle and the damage as the customers target is calculated on the target tracts. At the same time, the damage of the engine rig test is measured. The rig test procedure and test time are adjusted to make the rig test damage equivalent to customers target damage. Optimization of the engine rig test method, considering the damage of high cycle fatigue, thermal mechanical fatigue, wear-abrasive, oil deposits. And make be equivalent between rig test and 2 million km customers' operating conditions. A customer-related engine durability rig-test procedure in China is developed.